Cse(h)ndes üzenetek : A 90-es évek cseh képzőművészete. - Ševčívková, Jana; Ševčík, Jiři; Budapest Kiállítóterem, Budapest (Budapest : Budapest Galéria, 1997)
Zonderman, Bert ; Kovanda, Jiři ; Skrepl, Vladimir ; Hlavina, Tomáš ; Kintera, Krištof ; Penilo, Pedro ; Dopitová, Milena ; Šimlová, Štěpánka ; Surůvka, Jiři
Czech Art in the '90s, 26. September - 26. October 1997, Budapest Kiállítóterem, Budapest
kunstcatalogus
Keywords: Tsjechië